Improving rowing performance by adjusting oar blade size and angle - van Nieuwburg, W. C. A. M.; van Spreuwel, B. J. J.; Tran, M. T. K.; Yang, M. D.; Greidanus, A.; Mulder, G.; Tummers, M. J.; Westerweel, J.; Suijker, W.; van Wijk, R. (Frontiers in Sports and Active Living, 2023)
The principal aim of the work presented here is to investigate and demonstrate that a forward tilted rowing blade would result in a more efficient and effective motion of the blade through the water that would result in a higher boat speed when an equal input power is provided. A 1:5 scaled rowing boat is used to determine the performance of rowing blades with different sizes and blade angles. This is used to validate the results of a previous study where the optimal blade angle of 15° with respect to the oar shaft was determined ( 1). The input power and speed of the rowing boat can be compared between original and modified oar blades. Measurements in a towing tank demonstrate that a modified rowing blade result in faster rowing by 0.4% at the same input power. Maintaining the same stroke rate, the improvement of the blade efficiency is compensated by using a 4-6% increased blade area to yield the same input power.